OMISSION IN THE ENGLISH SUBTITLE OF THE INDONESIAN MOVIE KELUARGA CEMARA (2018) - Rahmani, Dinda; Novalinda (Program Studi Sastra Inggris, 2025)
The objectives of this research is to identify and categories omission strategy based on experts model in the English Subtitle of the Keluarga Cemara movie. The method used in collecting the data is a non-participant observational method and the method used in analyzed the data was a translational identity method.The total number of subtitles in the Keluarga Cemara movie is 1084 subtitles. The amount of data analyzed using the omission in this research is 286 subtitles. Omission of Redundant words applied 67 times, Omission of Culture-Spesific References applied 96 times, and Omission of Emotional Fillers and Discourse maker applied 123 times. However, Omission of Difficult-to-Translate Idioms of Expression and Omission to Avoid Long explaination is applied 0 times. this study indicated that the source language tended to exhibit repetition of words or phrases that were not typically used in the target language. As a result, omission was employed to ensure the acceptability of the translation to target language speakers. The translator showed a tendency to omit expressions deemed unnecessary for translation due to the high frequency of lexical repetition in the source language. Additionally, the translator omitted certain utterances by actors in the film, as they were delivered in the TL.